Limonene inhibits Candida albicans growth by inducing apoptosis - Thakre, Archana; Zore, Gajanan; Kodgire, Santosh; Kazi, Rubina; Mulange, Shradha; Patil, Rajendra; Shelar, Amruta; Santhakumari, Bayitigeri; Kulkarni, Mahesh J.; Kharat, Kiran; Karuppayil, Sankunny Mohan (Medical Mycology, 2018)
Anti-Candida potential of limonene was evaluated against planktonic growth, biofilm (adhesion, development and maturation) and morphogenesis of Candida albicans in this study. Limonene is a major constituent of citrus oil and most frequently used terpene in food and beverage industry due to its pleasant fragrance, nontoxic, and is generally recognized as safe (GRAS) flavoring agent as well as treatment option in many gastrointestinal diseases. Limonene exhibited excellent anti-Candida activity and was equally effective against planktonic growth of C. albicans isolates differentially susceptible to FLC (N = 35). Limonene inhibited morphogenesis significantly at low concentration. However, it showed stage dependent activity against biofilm formation, that is, it was more effective against adhesion followed by development and maturation. Limonene also exhibited excellent synergy with FLC against planktonic and biofilm growth. SWATH-MS analysis led to identification of limonene responsive proteins that provided molecular insight of its anti-Candida activity. Proteomic analysis revealed upregulation of proteins involved in cell wall glucan synthesis (Kre6); oxidative stress (Rhr2, Adh7 and Ebp1); DNA damage stress (Mbf1 and Npl3); nucleolar stress (Rpl11, Rpl7, Rpl29, Rpl15) and down regulation of cytoskeleton organization (Crn1, Pin3, Cct8, Rbl2), and so forth, in response to limonene. Limonene mediated down regulation of Tps3 indicates activation of caspase (CaMca1) and induction of apoptosis in C. albicans. These results suggest that limonene inhibits C. albicans growth by cell wall/membrane damage induced oxidative stress that leads to DNA damage resulting into modulation of cell cycle and induction of apoptosis through nucleolar stress and metacaspase dependent pathway.

Serum responsive proteome reveals correlation between oxidative phosphorylation and morphogenesis in Candida albicans ATCC10231 - Ahmed, Radfan; Kodgire, Santosh; Santhakumari, B.; Patil, Rajendra; Kulkarni, Mahesh J.; Zore, Gajanan (Journal of Proteomics, 2018)
To understand the impact of fetal bovine serum (FBS) on metabolism and cellular architecture in addition to morphogenesis, we have identified FBS responsive proteome of Candida albicans. FBS induced 34% hyphae and 60% pseudohyphae in C. albicans at 30 C while 98% hyphae at 37 C. LC-MS/MS analysis revealed that 285 proteins modulated significantly in response to FBS at 30 degrees C and 37 degrees C. Out of which 152 were upregulated and 62 were downregulated at 30 degrees C while 18 were up and 53 were downregulated at 37 degrees C. Functional annotation suggests that FBS may inhibit glycolysis and fermentative pathway and enhance oxidative phosphorylation (OxPhos), TCA cycle, amino acid and fatty acid metabolism indicating a use of alternative energy source by C. albicans. OxPhos inhibition assay using sodium azide corroborated the correlation between inhibition of glycolysis and enhanced OxPhos with pseudohyphae formation. C. albicans induced hyphae in response to FBS irrespective of down regulation of Rasl,Asrl/Asr2, indicates the possible involvement of MAPK and cAMP-PKA independent pathway. The Cell wall of cells grown in presence of FBS at 30 degrees C was rich in mannan, Beta 1,3glucan and chitin while membranes were rich in ergosterol compared to those grown at 37 degrees C. Significance of the study: This is the first study suggesting a correlation between OxPhos and morphogenesis especially pseudohyphae formation in C. albicans. Our data also indicate that fetal bovine serum (FBS) induced morphogenesis is multifactorial and may involve MAPK and cAMP-PKA independent pathway. In addition to morphogenesis, our study provides an insight in to the modulation of metabolism and cellular architecture of C. albicans in response to FBS.
Keywords: analysis; Candida albicans; Fetal bovin serum; Liquid chromatography mass spectrometry; morphogenesis; Oxidative phosphorylation; pathogenicity

Oxidative stress induced by piperine leads to apoptosis in Candida albicans - Thakre, Archana; Jadhav, Vyankatesh; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra; Kharat, Kiran; Zore, Gajanan; Karuppayil, S. Mohan (Medical Mycology, 2021)
Candida albicans is a member of pathogens with potential drug resistance threat that needs novel chemotherapeutic strategies. Considering the multifarious biological activities including bioenhancer activity, anti-Candida potential of piperine was evaluated against planktonic/biofilm and hyphal growth of C. albicans alone or in combination as a synergistic agent with fluconazole. Piperine inhibits planktonic growth at or less than 15 mu g/ml, hyphae induction at 5 mu g/ml concentration, and exhibits stage-dependent activity against biofilm growth of a fluconazole-resistant strain of C. albicans (ATCC10231). Though piperine couldn't kill inoculum completely at minimum inhibitory concentration (MIC), it is fungicidal at higher concentrations, as shown in apoptosis assay. FIC index values indicate that piperine exhibits excellent synergistic activity with fluconazole against planktonic (0.123) and biofilm (0.215) growth of an FLC resistant strain. Mode of anti-Candida activity was studied by identifying piperine responsive proteins wherein the abundance of 25 proteins involved in stress response, signal transduction and cell cycle were modulated (22 up and 3 downregulated) significantly in response to piperine (MIC50). Modulation of the proteins involved suggests that piperine affectsmembrane integrity leading to oxidative stress followed by cell cycle arrest and apoptosis in C. albicans. Flow cytometry-basedmitochondrialmembrane potential (MMP), cell cycle and apoptosis assay, as well as real-time quantitative polymerase chain reaction analysis of selected genes, confirms piperine induced oxidative stress (TRR1), cell cycle arrest and apoptosis (CaMCA1). Based on our results, we conclude that piperine inhibits planktonic and difficult-to treat-biofilm growth of C. albicans by affecting membrane integrity thereby inducing oxidative stress and apoptosis. Lay Abstract Piperine inhibit Candida albicans growth (planktonic and biofilm) significantly in our study. Piperine exhibits excellent synergistic potential with fluconazole The proteome analysis suggests that piperine induced membrane damage leads to oxidative stress followed by cell cycle arrest and apoptosis.
Keywords: Apoptosis; C. albicans; drug resistance; piperine; proteomics; synergy

Proteomic profile of candida albicans biofilm - Abdulghani, Mazen; Iram, Rasiqua; Chidrawar, Priti; Bhosle, Kajal; Kazi, Rubina; Patil, Rajendra; Kharat, Kiran; Zore, Gajanan (Journal of Proteomics, 2022)
Candida albicans biofilms are characterized by structural and cellular heterogeneity that confers antifungal resistance and immune evasion. Despite this, biofilm formation remains poorly understood. In this study, we used proteomic analysis to understand biofilm formation in C. albicans related to morphophysiological and architectural features. LC-MS/MS analysis revealed that 64 proteins were significantly modulated, of which 31 were upregulated and 33 were downregulated. The results indicate that metabolism (25 proteins), gene expression (13 proteins), stress response (7 proteins), and cell wall (5 proteins) composition are modulated. The rate of oxidative phosphorylation (OxPhos) and biosynthesis of UDP-N-acetylglucosamine, vitamin B6, and thiamine increased, while the rate of methionine biosynthesis decreased. There was a significant modification of the cell wall architecture due to higher levels of Sun41, Pir1 and Csh1 and increased glycosylation of proteins. It was observed that C. albicans induces hyphal growth by upregulating the expression of genes involved in cAMP-PKA and MAPK pathways. This study is significant in that it suggests an increase in OxPhos and alteration of cell wall architecture that could be contributing to the recalcitrance of C. albicans cells growing in biofilms. Nevertheless, a deeper investigation is needed to explore it further.Significance: Candida sps is included in the list of pathogens with potential drug resistance threat due to the increased frequency especially colonization of medical devices, and tissues among the patients, in recent years. Significance of our study is that we are reporting traits like modulation in cell wall composition, amino acid and vitamin biosynthesis and importantly energy generation (OxPhos) etc. These traits could be conferring antifungal resistance, host immune evasion etc. and thus survival, in addition to facilitating biofilm formation. These findings are expected to prime the further studies on devising potent strategy against biofilm growth among the patients.
Keywords: Biofilm; Candida albicans; Cell wall; LC-MS; Metabolism; MS; proteomics

Opaque cell-specific proteome of Candida albicans ATCC 10231 - Abdulghani, Mazen; Telang, Saraswati; Desai, Manisha; Kadam, Shivdas; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra; Maurya, Radheshyam; Zore, Gajanan (Medical Mycology, 2023)
Candida albicans, a polymorphic opportunistic pathogen of humans, can exist in different morphological forms like yeast, hyphae, pseudohyphae, chlamydospores, and white and opaque cells. Proteomic analysis of opaque form of C. albicans ATCC 10231 is carried out in the present study using microflow liquid chromatography-tandem mass spectrometry and validated using expression analysis of selected genes using reverse transcription quantitative real-time PCR and mitochondrial membrane potential assay. This is the first report identifying opaque cell-specific proteins of C. albicans. A total of 188 proteins were significantly modulated under opaque form compared to white cells, of which 110 were upregulated, and 78 were downregulated. It was observed that oxidative phosphorylation (OxPhos) and oxidative stress are enhanced in C. albicans cells growing under opaque form as proteins involved in OxPhos (Atp1, Atp3, Atp16, Atp7, Cox6, Nuc2, Qcr7, and Sdh12) and oxidative stress response (Gcs1, Gtt11, Gpx2, Sod1, Ccp1, and Lys7) were significantly upregulated. The maximum upregulation of 23.16- and 13.93-fold is observed in the cases of Ccp1 and Nuc2, respectively. The downregulation of proteins, namely Als1, Csh1, Sap9, and Rho1, determining cell surface chemistry indicates modulation in cell wall integrity and reduced adhesion of opaque cells compared to white cells. This study is significant as it is the first draft of the proteomic profile of opaque cells that suggests enhanced OxPhos, oxidative stress, and modulation in cell surface chemistry indicating reduced adhesion and cell wall integrity, which could be associated with reduced virulence in opaque form. However, a deeper investigation is needed to explore it further. Lay Summary Opaque form is one of the least studied morphological forms of Candida albicans. To the best of our knowledge, this is the first report providing opaque cell-specific proteome. It suggests enhanced oxidative phosphorylation, oxidative stress, and modulation in cell surface chemistry, which could be associated with reduced virulence in opaque form.
Keywords: albicans; C; LC-MS; MS; opaque; Oxidative stress; OxPhos; protein

Proteome dataset of Candida albicans (ATCC10231) opaque cell - Zore, Gajanan; Abdulghani, Mazen; Kodgire, Santosh; Kazi, Rubina; Shelar, Amruta; Patil, Rajendra (BMC Research Notes, 2024)
<h3 class="c-article__sub-heading" data-test="abstract-sub-heading" style="margin: 0px 0px 8px; box-sizing: inherit; font-size: 1.5rem; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, Oxygen-Sans, Ubuntu, Cantarell, "Helvetica Neue", sans-serif; line-height: 1.24; font-weight: 400;"> Objectives Candida albicans, a polymorphic yeast, is one of the most common, opportunistic fungal pathogens of humans. Among the different morphological forms, opaque form is one of the least-studied ones. This opaque phenotype is essential for mating and is also reported to be involved in colonizing the gastrointestinal tract. Considering the significance of the clinical and sexual reproduction of C. albicans, we have investigated the morphophysiological modulations in opaque form using a proteomic approach. <h3 class="c-article__sub-heading" data-test="abstract-sub-heading" style="margin: 24px 0px 8px; box-sizing: inherit; font-size: 1.5rem; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, Oxygen-Sans, Ubuntu, Cantarell, "Helvetica Neue", sans-serif; line-height: 1.24; font-weight: 400;"> Data description In the current investigation, we have used Micro-Liquid Chromatography-Mass Spectrometry (LC-MS/MS) analysis to create a protein profile for opaque-specific proteins. Whole-cell proteins from C. albicans (ATCC10231) cells that had been cultured for seven days on synthetic complete dextrose (SCD) medium in both as an opaque (test) and as a white (control) form cells were extracted, digested, and identified using LC-MS/MS. This information is meant to serve the scientific community and represents the proteome profile (SWATH Spectral Libraries) of C. albicans opaque form.